2017
DOI: 10.3390/ijms18081697
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Supplement in a Buffer for Dry Eye Syndrome Treatment

Abstract: Dry eye syndrome (DES) is one of the most common types of ocular diseases. There is a major need to treat DES in a simple yet efficient way. Artificial tears (AT) are the most commonly used agents for treating DES, but are not very effective. Herbal extractions of ferulic acid (FA), an anti-oxidant agent, and kaempferol (KM), an anti-inflammatory reagent, were added to buffer solution (BS) to replace ATs for DES treatment. The cytotoxicity and anti-inflammatory effects were examined in vitro by co-culture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In addition, both compounds were able to inhibit the UV-B induced oxidative stress in human corneal and conjunctival cells, in a dose-dependent manner [13]. Further, several studies have demonstrated the in vitro anti-inflammatory activity on human corneal cells of curcumin [71], DA-6034 (7-carboxymethyloxy-3 4 ,5-trimethoxy flavone) [72], Daidzin [73], EGCG [74][75][76][77], Pterostilbene [78], and a mixture of ferulic acid with kaempferol [79]. Catechin was also able to reduce Prostaglandin E2 production on rabbit cornea cells [80].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both compounds were able to inhibit the UV-B induced oxidative stress in human corneal and conjunctival cells, in a dose-dependent manner [13]. Further, several studies have demonstrated the in vitro anti-inflammatory activity on human corneal cells of curcumin [71], DA-6034 (7-carboxymethyloxy-3 4 ,5-trimethoxy flavone) [72], Daidzin [73], EGCG [74][75][76][77], Pterostilbene [78], and a mixture of ferulic acid with kaempferol [79]. Catechin was also able to reduce Prostaglandin E2 production on rabbit cornea cells [80].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Li et al 26 suggested radical scavenging agent against hyperosmolarity primary human corneal epithelial cells. Chen et al 27 later found that herbal extractions of ferulic acid, an anti-oxidant agent, and Kaempferol, an anti-inflammatory agent, were effective in dry eye treatment in rabbits.…”
mentioning
confidence: 99%
“…The richest plant sources of kaempferol are green leafy vegetables, such as spinach, kale, and herbs including dill, chives, and tarragon [ 121 ]. This polyphenol shows antioxidant, anti-inflammatory, cardioprotective, and anticancer properties [ 121 , 122 , 123 ]. However, still further clinical trials must be carried out to confirm its beneficial effects during clinical application at the aim to manage inflammatory-related diseases [ 124 ].…”
Section: Polyphenols’ Effects In Dedmentioning
confidence: 99%
“…Chen et al [ 122 ] studied the combination of two polyphenolic compounds: kaempferol and ferulic acid. The optimal combination has been experimentally set as 100 µM of ferulic acid plus 1 µM of kaempferol.…”
Section: Polyphenols’ Effects In Dedmentioning
confidence: 99%
See 1 more Smart Citation